PERSPEKTIF AGAMA DAN KEBUDAYAAN DALAM KEHIDUPAN MASYARAKAT INDONESIA (Suatu Tinjauan Sosiologi Agama) - Bauto, Laode Monto (Universitas Pendidikan Indonesia, 2014)
The relationship of religion, culture and community very important or is a system of life because of the interconnectedness of each other. But the question of keberagamaan and social development will not be complete if only seen from one particular aspect only. For that in looking at the question of societal must go through a holistic approach. Required studies as the study of the sociology of religion and vice versa. It means the study of the life of keberagamaan the community won't be completed without involving sociology, sociological stats helper monkeys do not judge the religion concerned. Each nation or group that actually live up to the mandate of each religion, therefore by itself will manifest harmony, brotherhood, peace and comfort in the life of bermayarakat. Because religions have taught the truth and goodness and distanced from all malice, strife, discrimination etc. Religious life looks on mindset, behaviour or attitude and way of living one's religious attitude embodiment and able to receive different neighbor any religion as a servant of God Almighty. Religion as a guide of human life created by God, the one true God through his life. Whereas culture is as a habit or an Ordinance of human life created by the man itself results from creativity, taste and karsanya given by the Lord. Religion and culture influence each other each other. Religion affects culture, community groups, and ethnic groups. The culture tends to be fickle to any people or groups who really lives in accordance with the mandate his religion each, hence will automatically be eventuate harmony, the peace and comfort in life bermayarakat. Because of religion have taught truth and goodness and removed from all philippic, dissensions, discrimination and others. Religious life looks on people think, behavior or attitude and manner embodiment attitude religious life someone and capable of receiving fellow different any religious as the servants of allah swt. Religion as a guideline human life created by god, of almighty god in lived his life. While culture is as habit or procedures of human life created by human beings themselves from the power copyright, taste and karsanya given by god. Religion and culture interplay each other. Religious affect culture, the group, and peoples. Culture capricious tending to any people or groups who really lives in accordance with each, amanah his religion hence with itself would be harmony, the fraternity, peace and comfort in life community. Because of religion have taught truth and goodness and badness, taking away from all dissensions, discrimination and others. Religious life seemed in a pattern of thought, of behavior or attitude and manner of living religious embodiment of the attitude of someone and capable of receiving a fellow who is different any religious a follower of allah swt. Religion as a guideline human life created by the lord of almighty god in lived his life. While culture is as the habit or procedures of human life created by human beings themselves from the power of copyright, taste and karsanya given by god. Religion and culture on each other. Affecting culture, religion community groups, and peoples.Keywords :Religion, cultural and society